HUBUNGAN TINGKAT STRES DAN AKTIVITAS FISIK DENGAN DISMENOREA DI MASA PANDEMI COVID-19 - Fadjriyaty, Tiara; Samaria, Dora (Jurnal Ilmiah Kesehatan Keperawatan, 2021)
Introduction: Dysmenorrhea is the medical term for pain with period or usually called menstrual pain. Some eligible womwn have had experience it. The pain is too much to bear that make women unable to do any activity. There are various factors that can aggravate dysmenorrhoea, such us smoking, dringking alcohol, lack of physical activity and stres. During the covid-19 pandemic, the government implemented several policies to reduce the spread of the Covid-19 virus, such as large-scale social restrictions so that most activities were carried out at home, these conditions can cause stress and lack of activity to change. The purpose of this study was to determine the correlation between stress levels and physical activity with the dysmenorrhoea scale in students of SMA Negeri 4 Tangerang Selatan during the Covid-19 pandemic.Methods: This study uses a cross-sectional research design with a sample of 128 respondents through the Consecutive Sampling method. The data was collected through google form using a questionnaire perceived stress scale 10 (PSS-10), the International Physical Activity Questionnaire (IPAQ) and the Numeric Rating Scale (NRS).Result: The results showed that there was a significant relationship between stress levels (p-value 0.019) and physical activity (p-value 0.039) with primary dysmenorrhoea scale..Discussion: Suggestions from this study are expected that students can control stress levels and increase daily physical activity because good physical activity will stimulate blood flow so that it can reduce and reduce menstrual pain (dysmenorrhea).Kata Kunci: Covid-19, physical activity, Primary Dysmenorrhea , Stress scale.